2016
DOI: 10.1186/s12917-016-0847-9
|View full text |Cite
|
Sign up to set email alerts
|

Localization of neonatal Fc receptor for IgG in aggregated lymphoid nodules area in abomasum of Bactrian camels (Camelus bactrianus) of different ages

Abstract: BackgroundThe neonatal Fc receptor (FcRn) plays a crucial role in transporting IgG and associated antigens across polarized epithelial barriers in mucosal immunity. However, it was not clear that FcRn expression in aggregated lymphoid nodules area (ALNA) in abomasum, a unique and important mucosal immune structure discovered only in Bactrian camels. In the present study, 27 Alashan Bactrian camels were divided into the following five age groups: fetus (10–13 months of gestation), young (1–2 years), pubertal (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In general, several studies show the involvement of FcRn in IgG transport in different tissues and cell types [ 15 , 16 , 17 , 18 , 19 ]. Thus, FcRn was also found to be expressed in the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…In general, several studies show the involvement of FcRn in IgG transport in different tissues and cell types [ 15 , 16 , 17 , 18 , 19 ]. Thus, FcRn was also found to be expressed in the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies about the different mucosal immune inductive sites of gastrointestinal tract has only received few attentions. Hence, based on our previous histological and structural studies of ALNA and ileal PPs in Bactrian camels [16,18,[21][22][23], 16S rDNA-Illumina Miseq sequencing was used to comparatively analyze the bacteria community characteristics in ALNA and ileal PPs of Bactrian camels, moreover, the biological information hidden in them were revealed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review focused on the role of FcRn in the nasal administration of biologics. For almost twenty years, researchers have demonstrated the involvement of FcRn in IgG transport in various tissues and cell types [ 7 , 11 , 32 , 70 , 71 ]. Accordingly, all of the studies included in this review demonstrated efficient transcytosis [ 9 , 15 , 16 , 26 , 27 , 28 , 29 , 35 , 46 , 61 , 69 ] of all of the biologics tested, irrespective of their molecular weight or the dose administered; therefore, they indicate that nasal administration may represent an efficient administration route for biologics for inducing both local and systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work demonstrated that intranasally applied low molecular weight peptides, e.g., oxytocin (1 kDa), readily access the CSF of rodents [ 71 , 92 ], monkeys [ 93 ] and humans [ 81 ]. In addition, the nasal route for biologics administration is not always successful.…”
Section: Discussionmentioning
confidence: 99%